2010
DOI: 10.1021/jp910614n
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen Storage in C2H4V and C2H4V+Organometallic Compounds

Abstract: The hydrogen storage capacity of C 2 H 4 V organometallic complex and its cation was obtained using second order Møller-Plesset (MP2) and density functional theory methods with different exchange and correlation functionals. A maximum of five and six hydrogen molecules can be adsorbed on C 2 H 4 V and C 2 H 4 V + compounds with gravimetric H 2 uptake capacities of 11.32 and 13.28 wt %, respectively. The effect of temperature and different exchange and correlation functionals on the adsorption energy of C 2 H 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 54 publications
(16 citation statements)
references
References 39 publications
0
16
0
Order By: Relevance
“…6). The complexes like Ti-polyacetylene complex [118], Scandium and vanadium based ethylene and propane complexes [119][120][121], alkane complexes [122][123][124], Sc atoms and Ti decorated on the C 60 and C 48 B 12 [125,126], niobium based ethene complex [127], TM-doped organosilica complexes [128], metal-decorated bucky balls [129,130] and multidecker Organometallic complexes are some of the well known hydrogen storing complexes. These complexes not only possess high binding energy but also have fast hydrogen adsorption and desorption cycles.…”
Section: Organotransition Metal Complexesmentioning
confidence: 99%
“…6). The complexes like Ti-polyacetylene complex [118], Scandium and vanadium based ethylene and propane complexes [119][120][121], alkane complexes [122][123][124], Sc atoms and Ti decorated on the C 60 and C 48 B 12 [125,126], niobium based ethene complex [127], TM-doped organosilica complexes [128], metal-decorated bucky balls [129,130] and multidecker Organometallic complexes are some of the well known hydrogen storing complexes. These complexes not only possess high binding energy but also have fast hydrogen adsorption and desorption cycles.…”
Section: Organotransition Metal Complexesmentioning
confidence: 99%
“…This is normally considered as an effect of exchange and correlation functional on the adsorption energy. Effect of exchange and correlation functional on adsorption energy was also reported earlier [40,41]. The adsorption energy per H 2 molecule with Gibbs free energy correction (ΔE G ) is calculated as concise where E G [X] stands for the energy of X with Gibbs free energy correction.…”
Section: Resultsmentioning
confidence: 85%
“…1) [15] In our recent work, we have estimated the averaged H 2 adsorption energy with Gibbs free energy correction (DG a ) of V-capped VC 3 H 3 complex using B3LYP and PBEPBE method at various temperatures. [6,7,15] Here, we have included BSSE-correction to DG a , assigned as DG a(BSSE) . Temperature dependence of DG a(BSSE) is shown in Figure 2.…”
Section: Resultsmentioning
confidence: 99%
“…Recent research has demonstrated that some transition metal (TM)-decorated organic materials can store hydrogen at levels exceeding those found in most materials currently being evaluated for hydrogen storage applications. It includes TM-ethylene, [3][4][5][6][7] TM-decorated polyacetylene, [8] TM-bulky balls. [9,10] A novel concept of storing hydrogen in organometallic systems was put forth by some research groups in which p-electron deficient system interacts strongly with the TM via Dewar coordination and hydrogen adsorptions on a complex via Kubas interactions.…”
Section: Introductionmentioning
confidence: 99%